(untitled) (Research, Society and Development, 2022)
Objective: to identify and characterize the elderly hospitalized in a medical clinic sector of a hospital of clinics, in terms of having eligible criteria and having been indicated for palliative care. Method: retrospective, descriptive and quantitative study. Data were collected through the investigation of electronic medical records of all elderly hospitalized from January to December 2019, in a medical clinic sector and filling out the Supportive and palliative care indications tool (SPICT) questionnaire. Descriptive analysis was performed to characterize the sample and Fisher’s Exact Test to assess the association between two categorical variables. Results: 379 medical records were evaluated, and of these, it was found that 146 (38.5%) elderly were eligible for palliative care. Of this sample, men predominated (63%), with a mean age of 73.9 years. The most frequent diagnosis was chronic obstructive pulmonary disease (17.8%) and the underlying disease was systemic arterial hypertension (67.8%). Of the 146 elderly eligible for palliative care, only 50 actually received the indication by the health team and from this sample, 68% had death as an outcome. Conclusion: less than half of elderly patients eligible for palliative care actually received the indication. It is essential that professionals have knowledge about the principles and indication of palliative care, in order to plan and implement adequate care and then provide a better quality of life for this profile of patients.